Exercise alleviates diabetic complications by inhibiting oxidative stress-mediated signaling cascade and mitochondrial metabolic stress in GK diabetic rat tissues - John, Annie; Howarth, Frank Christopher; Raza, Haider (Frontiers in Physiology, 2022)
Type 2 diabetes, obesity (referred to as ‘diabesity’), and metabolic syndrome associated with increased insulin resistance and/or decreased insulin sensitivity have been implicated with increased oxidative stress and inflammation, mitochondrial dysfunction, and alterations in energy metabolism. The precise molecular mechanisms of these complications, however, remain to be clarified. Owing to the limitations and off-target side-effects of antidiabetic drugs, exercise-induced control of hyperglycemia and increased insulin sensitivity is a preferred strategy to manage ‘diabesity’ associated complications. In this study, we have investigated the effects of moderate exercise (1h/day, 5 days a week for 60 days) on mitochondrial, metabolic, and oxidative stress-related changes in the liver and kidney of type 2 diabetic Goto-Kakizaki (GK) rats. Our previous study, using the same exercise regimen, demonstrated improved energy metabolism and mitochondrial function in the pancreas of GK diabetic rats. Our current study demonstrates exercise-induced inhibition of ROS production and NADPH oxidase enzyme activity, as well as lipid peroxidation and protein carbonylation in the liver and kidney of GK rats. Interestingly, glutathione (GSH) content and GSH-peroxidase and GSH reductase enzymes as well as superoxide dismutase (SOD) activities were profoundly altered in diabetic rat tissues. Exercise helped in restoring the altered GSH metabolism and antioxidant homeostasis. An increase in cytosolic glycolytic enzyme, hexokinase and a decrease in mitochondrial Kreb’s cycle enzyme was observed in GK diabetic rat tissues. Exercise helped restore the altered energy metabolism. A significant decrease in the activities of mitochondrial complexes and ATP content was also observed in the GK rats and exercise regulated the activities of the respiratory complexes and improved energy utilization. Activation of cytochrome P450s, CYP 2E1, and CYP 3A4 was observed in the tissues of GK rats, which recovered after exercise. Altered expression of redox-responsive proteins and translocation of transcription factor NFκB-p65, accompanied by activation of AMP-activated protein kinase (AMPK), SIRT-1, Glut-4, and PPAR-γ suggests the induction of antioxidant defense responses and increased energy metabolism in GK diabetic rats after exercise.